Kontribusi Inflasi dan Upah Terhadap Kemiskinan di Kabupaten Ngada Provinsi Nusa Tenggara Timur - Stefanus Gusti Ma (Program Studi Pendidikan Ekonomi, Universitas Flores, 2023)
This study analyzes how the influence of inflation and wages the number of poor people in Ngada Regency. The research method used in this data analysis uses ultiple linear regression analysis. The type of data used is a combination of time series data (2016-2020 period) and cross section (12 sub-districts) sourced from the Central Statistics Agency of Ngada Regency. The results of this study indicate that the positive coefficient of inflation is 4386,046, this means that if inflation increases by 1%, poverty will also increase by 4,386.046 %. While the wage coefficient is 0.141, this means that if wages increase by 1%, poverty will decrease by 14.1%. The conclusion of this study shows that inflation and wages have a simultaneous effect on poverty, while the partial effect of inflation has no effect on poverty while wages have an effect on poverty.